The Thermal Performance of Chinese Vernacular Skywell Dwellings - Gang Yao; Dongting Han; Li Zhang; Zhongcheng Duan (Advances in Civil Engineering)
The aim of this research was to investigate the thermal performance of Chinese vernacular skywell dwellings. This was done by the analysis of on-site measurements of the environmental performance and computer simulation of solar conditions of eight vernacular skywell dwellings in three villages in southeastern China—Xidi, Zhifeng, and Yuyuan. Through the discussion of several heat inputs and outputs, it can be concluded that evaporative cooling had a substantial influence on the temperature in the skywells of dwellings in Xidi and Zhifeng villages. In addition to the buffering of temperature by thermal mass, evaporative cooling was found to further reduce the fluctuation in temperature inside the skywell and is likely to have been the main reason that the mean dry bulb temperatures inside the skywells in these villages were lower than the mean external dry bulb temperatures. Moreover, the construction materials of Chinese vernacular dwellings (skywell wall, floor material, wooden column, and panels) are likely to be hygroscopic.